Government's views and comments on the findings and recommendations of the Political Bureau - Nigeria. Federal Republic (Lagos : Federal Government Printer, 1987)
The bureau was set up to review Nigeria's political history and identify the basic problems which have led to our failure in the past and suggest ways of resolving and coping with these problems among other terms.
nmn, 02/04/2019
Loans
Keywords: Politics and government; Economic policy; Representative government and representation; Political bureau; Nigeria